Distyrylbenzene-aldehydes: identification of proteins in water - Kumpf, Jan; Freudenberg, Jan; Bunz, Uwe H. F. (The analyst, 2015)
Three different, water soluble, aldehyde-appended distyrylbenzene (DSB) derivatives were prepared. Their interaction with different albumin variants (human, porcine, bovine, lactalbumin, ovalbumin) was investigated (pH 11). All three fluorophores exhibit graded, protein-dependent fluorescence turn-on at slightly differing wavelengths. Linear discriminant analysis (LDA) differentiated all of the investigated albumins and was used to discern commercially available protein shakes. The three DSB derivatives barely react with the constituting amino acids but cysteine. In the proteins significant fluorescence signals are generated, probably due to a combination of imine/N,S-aminal formation and hydrophobic interactions between the DSBs and the proteins.
Gesehen am 03.06.2020